Evaluation of the Potential of Novel Co-Processed Excipients to Enable Direct Compression and Modified Release of Ibuprofen - Ivana Aleksić; Teodora Glišić; Slobodanka Ćirin-Varađan; Mihal Djuris; Jelena Djuris; Jelena Parojčić (Pharmaceutics)
Background/Objectives: Improving the production rates of modern tablet presses places ever greater demands on the performance of excipients. Although co-processing has emerged as a promising solution, there is still a lack of directly compressible excipients for modified-release formulations. The aim of the present study was to address this issue by investigating the potential of novel co-processed excipients for the manufacture of modified-release tablets containing ibuprofen. Methods: The excipients were prepared by melt granulation of lactose monohydrate with glyceryl palmitostearate as a binder. The influence of glyceryl palmitostearate particle size, ibuprofen content, compression pressure, and compression speed on the compaction behavior of the tablet blends was analyzed. Results: Novel co-processed excipients ensured good flowability and acceptable mechanical properties of the tablets containing up to 70% ibuprofen. Furthermore, lipid-based co-processed excipients proved to be very promising for directly compressible formulations with high-dose, highly adhesive active pharmaceutical ingredients such as ibuprofen, as they do not require additional lubricants. The influence of compression speed on the tensile strength of the tablets prepared was not pronounced, indicating the robustness of these directly compressible excipients. The investigated lipid-based excipients enabled a prolonged release of ibuprofen over 10 h. Conclusions: The novel lipid-based co-processed excipients have shown great potential for directly compressible formulations with modified release of high-dose, challenging active pharmaceutical ingredients.